2012
DOI: 10.1242/jeb.068742
|View full text |Cite
|
Sign up to set email alerts
|

Inducible tolerance to dietary protease inhibitors inDaphnia magna

Abstract: SUMMARYDaphnia has been shown to acquire tolerance to cyanobacterial toxins within an animalsʼ lifetime and to transfer this tolerance to the next generation. Here we used a strain of the cyanobacterium Microcystis aeruginosa, which contained two chymotrypsin inhibitors (BN920 and CP954), the green alga Scenedesmus obliquus as reference food and a clone of D. magna to investigate the physiological mechanism of acquired tolerance to these cyanobacterial toxins. The intracellular concentrations of CP954 and BN92… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
57
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 45 publications
(62 citation statements)
references
References 56 publications
5
57
0
Order By: Relevance
“…Additionally, our study indicates that such adaptation also appears within an ecosystem with a different spatial distribution of blooms. These new facets of the Daphnia-Microcystis interaction may be crucial for the stabilisation of the top-down effect of grazers in the trophic structure, for the limitation of microcystin accumulation by Daphnia and thus for the reduction of the contribution of daphniids to the transfer of toxins to higher trophic levels in food webs [6], [9], [46].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, our study indicates that such adaptation also appears within an ecosystem with a different spatial distribution of blooms. These new facets of the Daphnia-Microcystis interaction may be crucial for the stabilisation of the top-down effect of grazers in the trophic structure, for the limitation of microcystin accumulation by Daphnia and thus for the reduction of the contribution of daphniids to the transfer of toxins to higher trophic levels in food webs [6], [9], [46].…”
Section: Discussionmentioning
confidence: 99%
“…Control liposomes were produced according to [25] and subsequently enriched tenfold through centrifugation and subsequent resuspension in 1 ml liposome buffer [47]. For passive loading of the liposomes with microcystin, 500 μl of this suspension were added to 3 μg MC-LR and incubated for four h at 60°C.…”
Section: Methodsmentioning
confidence: 99%
“…Schwarzenberger et al [14] found that the tolerance of different Daphnia genotypes depended on the residual activity of proteases; increased gene expression and enhanced activity of the non-inhibited protease type also seemed to play a role. Von Elert et al [25] demonstrated that tolerance to cyanobacterial protease inhibitors was acquired by remodelling the affected digestive protease type.…”
Section: Introductionmentioning
confidence: 99%
“…These serine proteases represent the most important digestive enzymes in the gut of D. magna (Von Elert et al, 2004). When ingested with food particles, protease inhibitors negatively affect Daphnia by decreasing protease activity and reducing somatic growth (Lürling, 2003;Rohrlack et al, 1999;Von Elert et al, 2012;Schwarzenberger et al, 2012). The inhibition of digestive enzymes by these protease inhibitors should result in lower availability of amino acids.…”
Section: Introductionmentioning
confidence: 99%